Exploring critical success factors in compliance-driven cyber insurance within Malaysian organizations: A COBIT 5 enabler approach - Hamid, Nor Hasnul Azirah Abdul; Mazita, Mokhtar; Wan Khairul Anuar, Wan Abd Manan; Husna, Hashim (e-International Publishing House, 2025)
In today's cybersecurity landscape, simply acquiring cyber insurance is insufficient; its effectiveness relies on adherence to cybersecurity standards. This study explores critical success factors (CSFs) for compliance-driven cyber insurance in Malaysian organizations using the COBIT 5 enablers. The research identifies key factors essential for effective compliance-driven cyber insurance implementation through semi-structured interviews with industry experts. The findings align ten themes and seventeen sub-themes from qualitative analysis with the seven COBIT 5 enablers, emphasizing a holistic approach to enhance governance, risk management, and organizational resilience. This research offers valuable insights for organizations aiming to strengthen cyber resilience through compliance-aligned insurance strategies.